Application of harmonized fighting system against pomegranate orchard - Mirzaeva S.A; Kambarova, M.X; Irgashev, M.U; Rasulova, M.B (Indonesian Journal of Innovation Studies, 2019)
Pomegranate fruit is a monophage, and at the same time is also a typical carpophage, that is, the fruit is a moth. During the season, the pomegranate fruit develops from the 5th generation in full and in part from the 6th generation. In order to protect the pomegranate from pomegranate fruit, it is desirable to support all methods of the adaptive protection system (in particular: organizational-economic, agrotechnical, physico-mechanical, biological and chemical), bringing the number of pests to IZMM and below.